Visual design of a performance at the school theater - Aleksandra B. Nikitina (Управление культурой)
The article is addressed to leaders and teachers of children's theater groups, teachers of the educational field "Art", teachers of universities and colleges who train specialists for theatrical work with children, advisers to school directors for educational work, heads of festivals of children's theatrical creativity. The question of creating scenery , costumes, make-up in a theater performance where children play is considered in the article. Who and why should create projects, sketches and artistic and material objects themselves: the head of the children's theater group, pupils, parents, professional artists? The process is seen as educational, not technical. And all participants in the process are considered as participants in a single educational process: not only children, but also adults. The creation of the artistic design of the performance is considered as a part of the creation of a special CO-EXISTENCE open artistic educational environment, which is possible only with the jointly distributed activities of children and adults. The article provides a historical background on how this issue was considered from the beginning of the 20th century to the present day. Special attention in the historical part is paid to the question of what parameters and characteristics the design of performances should have, created for different age groups of schoolchildren. Then the article tells a story about a creative game dedicated to this issue, which was held at the tenth anniversary All-Russian Conference of School Theater Pedagogics in memory of Leopold Antonovich Sulerzhitsky in 2022. The conference was organized by the Laboratory of Socio-Cultural Educational Practices of the Research Institute of Urban Studies and Global Education of the Moscow City Pedagogical Institute and ANO Prolog. The conference is always held in an unusual format, full of creative practices and experiments, which are characterized by research by means of the theater and the play. In the form of such an exploratory game based on a modified debate (according to Karl Popper), the issue of modern practices in creating the visual design of a performance in children's theater groups was investigated. The issue was considered in the context of modern government decrees on the development of school theater.